Prevalence of overweight and obesity in a Mexican prison - AJ Argüello-González; MA García-Zazueta (Sociedad Española de Sanidad Penitenciaria, 2020)
ABSTRACT Objectives: Overweight and obesity constitute a public health problem; There are few prevalence studies of inmates. The objectives of this study are to determine the prevalence of overweight and obesity amongst inmates of the Islas Marias Prison Complex and to evaluate the waist-to-hip ratio (WHR) and the waist-to-height ratio (WHtR) as diagnostic measurements for abdominal obesity in this population. Material and method: Analytical, retrospective cross-sectional study at Rural Hospital No. 20 Islas Marias Nayarit, Mexico, with 426 cases from January 2016 to March 2017, who were male inmates from 18 to 73 years of age. The following ratios were calculated: BMI, WHR WHtR. A descriptive analysis was carried out for quantitative variables, frequencies and percentages by group, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), Youden index, positive and negative likelihood ratios of WHR and WHtR; ANOVA F test, Student's t-test, ROC curve, STROBE statement, SPSS v. 22. Results: 51.41% cases presented as overweight, 25.35% were obese, the cut-off point was 0.935 for WHR (s = 0.833; e = 0.717) and 0.545 for WHtR ICA (s = 0.981; e = 0.818). WHtR showed a good performance according to the Youden index. Discussion: There was a high prevalence of overweight and obesity in prisoners at the Islas Marias Prison Complex, WHtR showed better performance than WHR for diagnosing abdominal obesity. It is suggested that measurement of WHI should be included in daily medical practice.